PEMANFAATAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Andarwati, Nanik; Pujilestari, Yulita (Universitas Negeri Surabaya (Unesa), 2023)
In learning Pancasila and Civic Education, the majority of teachers deliver subject matter only guided by the sibulus program, RPP in accordance with the curriculum assisted by package books and LKS books. However, teachers do not use visual learning media so that the learning atmosphere is less interesting, boring, and the subject matter is difficult to understand. Teachers are required to have the ability and competence in creating active, creative, and innovative learning media. The Canva application is one of the supporting applications in developing electronic-based learning media. The Canva application can be used to design learning media for Pancasila and Civic Education. Canva is not only suitable for slide presentations, but it can also be used to create posters, infographics, learning resource cards, and so on. With these various options, teachers can present material in a more diverse and interesting way. The research method taken is research aimed at describing and analyzing phenomena, events, activities, perceptions, thoughts of people individually, and in groups. Qualitative research is a problem that arises from the data left open by the researcher. The subject of this research was carried out at SMP Nusantara Plus in South Tangerang. This research instrument uses interviews. With the results of the research that Pancasila and Civic Education Teachers at SMP Nusantara Plus South Tangerang city agree with the existence of electronic-based learning media, such as the Canva application to help teachers design effective learning media to increase interest in learning Pancasila and Civic Education in SMP Nusantara Plus Students in South Tangerang city. As for the use of this Canva application for responses from grade VII.2 students of SMP Nusantara Plus South Tangerang city that learning using electronic-based Pancasila and Civic Education learning media interests and curiosity.